Weathering of a carbon nanotube/epoxy nanocomposite under UV light and in water bath: impact on abraded particles. Issue 44 (22nd October 2015) - Schlagenhauf, Lukas; Kianfar, Bahareh; Buerki-Thurnherr, Tina; Kuo, Yu-Ying; Wichser, Adrian; Nüesch, Frank; Wick, Peter; Wang, Jing
Abstract : Weathering processes can influence the surface properties of composites with incorporated nanoparticles. Abstract : Weathering processes can influence the surface properties of composites with incorporated nanoparticles. These changes may affect the release behavior of nanoparticles when an abrasion process is applied. Therefore, the influence of two different weathering processes, immersion in water and exposure to UV light, on the properties of abraded particles from a carbon nanotube (CNT)/epoxy nanocomposite was investigated. The investigation included the measurement of the weathering impact on the surface chemistry of the exposed samples, the particle size of abraded particles, the quantity of exposed CNTs in the respirable part of the abraded particles, and the toxicity of abraded particles, measured by in vitro toxicity tests using the THP-1 monocyte-derived macrophages. The results showed that weathering by immersion in water had no influence on the properties of abraded particles. The exposure to UV light caused a degradation of the epoxy on the surface, followed by delamination of an approx. 2.5 μm thick layer. An increased quantity of exposed CNTs in abraded particles was not found; on the contrary, longer UV exposure times decreased the released fraction of CNTs from 0.6% to 0.4%. The toxicity tests revealed that abraded particles from the nanocomposites did not induce additional acute cytotoxic effects compared to particles from the neat epoxy.